(untitled) (Research, Society and Development, 2020)
To describe the epidemiological profile of meningitis in children under the age of five resident in the State of Paraiba between 2007 and 2017. A time series analysis in a descriptive epidemiological study, whose population comprised all the cases confirmed by the Executive Management of Health Surveillance of Paraiba. The obtained sample was analyzed through statistical resources using the SPSS software version 18.0. The age group indicated an increased concentration in children under the age of 1year old, corresponding to a coefficient of incidence of 24.1/10.000 habitants. The criteria of confirmation indicated 44.3% by means of the chemical and cytological examination, 77.6% progressed to hospital discharge and 9.8% to death. Regarding the temporal distribution of the cases, the year 2012 appears with the highest number of confirmed cases 20.06% and 2015 presented the lowest incidence 3.61%, within the period studied. The combat of Meningitis is still characterized as a relevant issue in the State, despite the declining tendency of confirmed cases, the incidence may still be considered as being high due to the vaccine protection that is available.